The Papyrus of the Treasury Scribe Iry-Iry: A New Ramesside Source for a Memphite Hymn to Osiris and the Book of Caves (BD 168). Issue 1 (June 2018) - Scalf, Foy
A publication of the papyrus of Iry-Iry in full with accurate identification of its contents. As a result, a Memphite hymn to Osiris has been identified from several sources gathered together with P. Iry-Iry. In addition, a new source for the introductory section of the Book of Caves (BD 168) has been discovered, known previously only from the papyrus of Bakenmut. This article provides a full discussion of the papyrus of Iry-Iry as well as a comparative edition of parallel manuscripts for the two compositions it contained.